INDEKS PENGUNGKAPAN PELAPORAN KEUANGAN BERBASIS WEB PERUSAHAAN SEKTOR INDUSTRI DASAR DAN KIMIA DI BEI - Nisa, Nur Fadilatun; Probowulan, Diyah; Zulkarnaeni, Achmad Syahfrudin (Fakultas Ekonomi dan Bisnis, 2023)
This study aims to measure the disclosure of reports on the company's financial website for basic and chemical subsector companies listed on the IDX. IFR (Internet Financial Reporting) is an alternative media that deals directly between investors and companies more efficiently and effectively. Internet Financial Reporting (IFR) is classified as Voluntary Disclosure, because its purpose is to be able to provide additional information to improve the quality of reporting. The samples used in this study were 85 basic and chemical subsector companies that disclosed their financial reports on the IDX. This study was designed using descriptive analysis, with content analysis. By hiding the components of financial disclosure on each of the basic chemical and industrial websites that are the research samples. Based on the results of the analysis that has been carried out, it shows that there are still many companies in the basic and chemicals subsectors that have not properly implemented Internet Financial Reporting, assessing 46 scores. companies whose IRI is above average and 39 companies whose IRI scores are below average so that there are still many companies that get an index score below the average on their financial statements.